Awareness towards a takaful protection among flood victims in the East-Coast Region in Malaysia: a preliminary analysis - Che Mohd Salleh, Marhanum; Kassim, Salina; Mustapha Kamil, Bidayatul Akmal; Razali, Siti Salwani; Che Embi, Nor Azizan (2016)
Climate change has intensified the risk of natural disasters all over the world. In Malaysia, there has been frequent large scale flooding in the recent years that resulted in damage in property and giving impact on the livelihood of the people, particularly in the east-coast regions of the country. In the absence of adequate social safety-nets, the low income people staying in the flood-prone areas find themselves not able to cope with the damage caused by the recurring floods. The objective of this study is twofold. First, it aims to investigate the impact of the flood on the socio-economic livelihoods of the victims, and second, to explore the awareness among the flood victims towards a Takaful protection to enable them to better cope with the flood risks. In methodology, we adopt a survey method on 147 respondents who were affected by the flood in the flood-prone areas in the states of Kelantan and Pahang. Based on simple descriptive analysis, it is found that flood had affected the victims financially as well as in terms of their source of income. In terms of awareness towards Takaful schemes, majority of the victims are aware of Takaful, yet about 30 percent of them are uncertain about the existence of Takaful schemes that may reduce their financial losses when the flood hit. Furthermore, the victims also have limited knowledge on the amount of Takaful contribution that they have to pay for flood coverage (41 percent) and they are uncertain on their capability to pay the monthly Takaful contribution in future (44 percent). The findings of this study provide important inputs on the possibility of establishing an affordable micro-takaful meant for future financial protection as a safety net especially for the lower income and most vulnerable flood victims in the country.